PENGARUH FASILITAS KESEHATAN DAN KUALITAS PELAYANAN TENAGA MEDIS KLINIK PERMATA UPGRIS TERHADAP KEPUASAN MAHASISWA MANAJEMEN UNIVERSITAS PGRI SEMARANG - Puspita Jati Dwi Ningsih; Nanik Iriyanti, Rauly Sijabat (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
The purpose of this study is to examine the effects of healthcare facilities and the quality of medical services at the Permata Clinic UPGRIS on the satisfaction of Management students at PGRI University Semarang. A quantitative approach was used in this study in the form of a survey by distributing questionnaires. This type of research is descriptive-analytic with total sampling as the sampling method and was conducted using the SPSS 22 software for data analysis. The method used to examine the data was multiple regression analysis, simultaneous testing with the F-test, and the coefficient of determination to determine the level of influence of the variables. The results of the analysis indicate that both variables significantly influence student satisfaction simultaneously (p < 0.05), with a contribution of 51.8% in explaining its variability. However, approximately 48.2% of satisfaction variation may be caused by other factors not examined in this study. In conclusion, while healthcare facilities and medical services are important and have a significant role, it cannot be denied that other factors also play a role in determining student satisfaction